Implementing Scrum in Government Institution: The Case of the Directorate General of Tax - Syafrudin, Amir; Kurnia, Hertina R; Sunaryo, Dodik (IJTB (International Journal of Technology And Business), 2017)
Any software developed within the Directorate General of Tax (DGT) should be consistent with the requirements of the organization and their users. However, changes to business processes, regulations, and other factors are unpredictable and they might cause unexpected changes in the requirements. In Waterfall methodology, these unexpected changes might be difficult to accommodate because Waterfall methodology uses a sequential and all-at-once approach for developing software. In order to avoid such circumstances, the DGT should implement an iterative and incremental approach that is inherent in Scrum methodology. This paper describes an early implementation of Scrum methodology in the DGT. It explains some of the advantages and obstacles faced by the DGT during the implementation. It also provides several recommendations for the DGT to ensure the successful transition from Waterfall to Scrum which includes technical, behavioral, and organizational changes